2017
DOI: 10.31729/jnma.2987
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malnutrition in a Rural Residential Sanskrit School in Baglung, Nepal

Abstract: Introduction:Under-nutrition is a condition in which there is inadequate consumption, poor absorption or excessive loss of nutrients. Nepal still faces high chronic as well as acute undernutrition in children. The following study was conducted a Sanskrit school in rural Baglung to find the prevalence of malnutrition among the children which could reflect the nutritional status of the community.Methods: Out of 60 students admitted to the school, only 43 were present at the time when we collected our data. Weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…It also reported that studying in private schools and having a family income of more than ten thousand Nepalese rupees were strongly associated with overweight/obesity 59 . Contrary to these studies, a study done in a Sanskrit school in Baglung illustrated that no student was either obese or overweight 60 . However, many students were found to be undernourshied 60 .…”
Section: Prevalence Of Over-nutrition Among Children In Nepalmentioning
confidence: 86%
See 2 more Smart Citations
“…It also reported that studying in private schools and having a family income of more than ten thousand Nepalese rupees were strongly associated with overweight/obesity 59 . Contrary to these studies, a study done in a Sanskrit school in Baglung illustrated that no student was either obese or overweight 60 . However, many students were found to be undernourshied 60 .…”
Section: Prevalence Of Over-nutrition Among Children In Nepalmentioning
confidence: 86%
“…Contrary to these studies, a study done in a Sanskrit school in Baglung illustrated that no student was either obese or overweight 60 . However, many students were found to be undernourshied 60 . Another study among pre-school children in Bhaktapur showed that prevalence of overweight was 4.1%.…”
Section: Prevalence Of Over-nutrition Among Children In Nepalmentioning
confidence: 86%
See 1 more Smart Citation
“…In the 8 sample studies, most articles discuss sociodemographies where school children who live in rural areas tend to experience stunting compared to children who live in cities. This is due to family characteristics, such as the education of mothers and fathers who are still lacking, income and low employment of parents in the research conducted by Herrador [3], [5], [8]. The prevalence of malnutrition was significantly higher in rural than in urban communities (53%) [5].…”
Section: Sosiodemographic Characteristicsmentioning
confidence: 98%
“…We identified 10 articles analyzed the consumption variable also affects stunting in school children. A study in Egypt indicated that stunted children was significanty higher in participants with poultry consumption less than three times per week 45,9% dan infrequent fruit consumption 37,8% [3]. In addition to consuming foods containing macro nutrients such as carbohydrates, protein and fat, the intake of various vitamins and minerals also affects the nutritional status of school children.…”
Section: Consumptionmentioning
confidence: 99%